In vitro reactivity of ventral aorta to acetylcholine and noradrenaline in yellow freshwater eel (Anguilla anguilla L.) acclimatized to 10.1 MPa hydrostatic pressure. - Guerrero, F.; Theron, M.; Sebert, P. (HAL CCSD, 2000)
International audience We examined in vitro vascular reactivity of eels previously acclimatized to 10.1 MPa hydrostatic pressure (HP) for 21 days. The isometric tension developed by ventral aortic rings was measured at atmospheric pressure. Dose-response curves for either acetylcholine (ACh) or noradrenaline (NA), as well as contractions evoked by 80 mM K+, were compared with time-matched experiments conducted on rings obtained from control eels. Results showed that neither the optimal tension nor the maximal force of the K+-evoked contraction were significantly modified, suggesting that acclimatization to high HP did not change the vascular smooth muscle contractile machinery. The dose-response curve to ACh was not significantly changed. Conversely, although NA always relaxed aortic rings, the response of acclimatized eels was significantly reduced over the entire range of the agonist concentration tested (10(-8) to 10(-3) M), except for the lowest one (10(-9) M). The maximal amplitude of the NA-induced relaxation was significantly reduced in aortic rings from acclimatized eels as compared with non-acclimatized samples (339.3 +/- 86.5 vs. 744.3 +/- 72.1 mg x mg(-1) dry weight, P < 0.005). Our results suggest that acclimatization to high HP could selectively alter the control of vascular tone by catecholamines.